Baryogenesis - Fong, Chee Sheng (Cadernos de Astronomia, 2023)
The standard model of particle physics describes matter and antimatter as coming from the same fields and this fact has been confirmed experimentally. It is then curious that the observable universe is made of matter and not antimatter. We will first discuss the evidence that we live in a matter-dominated (or matter-antimatter asymmetric) Universe and then proceed to discuss if this can be explained according to our current understanding of the cosmology and particle physics. We will argue that an important process known as baryogenesis to generate a cosmic matter-antimatter asymmetry had to occur before the Universe was a few second old. Then, we will discuss the necessary ingredients for a successful baryogenesis and point out that the current model contains all the ingredients but not in a sufficient amount. Finally, we will discuss possible extensions to the current model which allow successful baryogenesis and how they can be tested experimentally. Interestingly, they might also be connected to other open puzzles in the fundamental physics, like the tiny neutrino mass.
Keywords: baryogenesis; matter and antimatter asymetry; primordial universe